Tripling the Bioavailability of Rosuvastatin Calcium Through Development and Optimization of an In-Situ Forming Nanovesicular System - Ibrahim Elsayed; Rania Moataz El-Dahmy; Ahmed Hassen Elshafeey; Nabaweya Abdelaziz Abd El Gawad; Omaima Naim El Gazayerly (MDPI AG, 2019)
In situ forming nanovesicular systems (IFNs) were prepared and optimized to improve Rosuvastatin calcium (RC) oral bioavailability through increasing its solubility and dissolution rate. The IFN was composed of Tween® 80 (T80), cetyl alcohol (CA), in addition to mannitol or Aerosil 200. A single simple step was adopted for preparation, then the prepared formulations were investigated by analyzing their particle size (PS), polydispersity index (PDI), Zeta potential (ZP), entrapment efficiency (EE), and flowability properties. D-optimal design was applied to choose the optimized formulations. The maximum desirability values were 0.754 and 0.478 for the optimized formulations containing 0.05 g CA, 0.18 g T80, and 0.5 g mannitol (OFM) or Aerosil (OFA), respectively. In vitro drug release from the optimized formulations showed a significantly faster dissolution rate when compared to the market product. In vivo performance of the optimized formulations in rabbits was investigated after filling them into enteric-coated capsules. Ultimately, OFA formulation achieved a 3 times increase in RC oral bioavailability in comparison with the market product, supporting the hypothesis of considering IFNs as promising nanocarriers able to boost the bioavailability of BCS class II drugs.